Ectopic mediastinal parathyroid: A case report of recurrent secondary hyperparathyroidism - Stephen Kwak, MD; Elliot K. Fishman, MD (Radiology Case Reports, 2023)
Ectopic mediastinal parathyroid is a common cause of recurrent and persistent hyperparathyroidism. Patients with recurrent and persistent hyperparathyroidism have elevated parathyroid hormone, which results in bone, vascular, and soft tissue abnormalities. While CT and MRI can be used to investigate ectopic parathyroid tissue, nuclear medicine Technetium-99m Sestamibi scan is the preferred method of imaging with sensitivity of 80%-90% and specificity of nearly 90%. Once identified, ectopic mediastinal parathyroid is treated with surgical resection though less invasive methods have gained popularity. We present a case of a 62-year-old female with recurrent secondary hyperparathyroidism that was localized to an ectopic mediastinal parathyroid gland.